Elements, functions, and linguistic forms of the discourse structure in Indonesian food vlogs - Listiyorini, Ari; Wijana, I Dewa Putu; Hardjanto, Tofan Dwi (LITERA, 2024)
The study is aimed at identifying the elements, functions, and language forms of the discourse structure of the food vlogs of four Indonesian YouTubers. The study used the descriptive qualitative research design. Data sources were 16 videos of four Indonesian vloggers Nex Carlos, Mgdalenaf, Ria SW, and Tanboy Kun. Data were in the forms of utterances in the food vlogs.  The research instrumens were human instruments, hardware tools and software devices. Data were elicited by the techniques of recording, transcribing, reading, and note taking. Data were analyzed by using the distribution and comparison techniques. Data validity was appraised by minute observation, triangulation, and peer reviews. Results are as follows. First, the structural elements of the food vlog discourse are opening, content, and closing. Second, functions that are found in the three elements are building interaction with viewers, presenting preliminary information of videos, introducing topics, asking viewers to watch videos to the end, informing about the location of the food being reviewed, describing the food being reviewed, giving comments concerning the food being reviewed, recommending the food/food place, asking viewers to give responses, and thanking reviewers. Third, linguistic features being used in each discourse element and structural function of the food vlog discourse are greetings, usernames or YouTube channels, lexicon referring to location, time and directions, and food being reviewed. Fourth, speech acts used in the discourse include assertive illocutionary acts for informing, directive illocutionary acts for requesting and recommending, and expressive illocutionary acts for praising, criticizing, and thanking.  Code mixing is used in the discourse to create informal and relaxing situation and atmosphere.